Supply chain resilience: Conceptualization and scale development using dynamic capability theory - Chowdhury, M.; Quaddus, Mohammed (Elsevier, 2017)
© 2017 Elsevier B.V.A growing number of researchers and practitioners have placed supply chain resilience (SCRE) at the forefront of their research agendas due to an increased susceptibility to disruptive events in global supply chains. However, empirical research in this area has been affected by the lack of a validated measurement model. In this context, drawing on dynamic capability theory, this research develops a measurement instrument for SCRE. This research conducts a qualitative field study, followed by a quantitative survey. Content analysis is used to explain various dimensions in the qualitative field study, and partial least squares (PLS)-based structural equation modelling (SEM) is used to analyse the data collected in the quantitative survey. The research is conducted with three rounds of data collection and analyses. The results show that SCRE is a multidimensional and hierarchical construct, which consists of three primary dimensions: proactive capability, reactive capability and supply chain design quality. These three primary dimensions are further operationalized through twelve sub-dimensions. The findings also affirm that the SCRE scale potentially better predicts supply chain operational vulnerability (OV) and supply chain performance (SCP) and conforms to the “technical” and “evolutionary” fitness criteria of dynamic capability theory. The implications of these findings are discussed in the context of theory and practice. Limitations and future avenues of research are also discussed.